Early Laboratory Biomarkers as Risk Factors for Alzheimer's Disease: A Systematic Review and Meta-analysis - Ali, Abdalla Eltoum; Abdalla , Baraa; Ahmeid, Mutaz Sabah; Hamza , Alneil M.; Mohieldein, Abdelmarouf; Modawe, Gadalla (AL-Kindy College Medical Journal, 2026)
The timely diagnosis of Alzheimer's disease is of paramount importance to support the timely intervention and effective risk management strategies. Biomarkers have become powerful tools for predicting the risk of Alzheimer's disease.The objective of this systematic review and meta-analysis is to examine the prognostic utility of early laboratory biomarkers in Alzheimer's disease, how integrated into risk assessment models, and the gaps in modern studies.An extensive search was conducted in databases such as PubMed, Scopus, and Web of Science to retrieve peer-reviewed articles published since 2014. There were 26 empirical studies that met the determined inclusion criteria and were aimed at the investigation of tau protein, amyloid-beta (Ab42), phosphorylated tau (p-tau), neurofilament light chain (NfL), Apolipoprotein E (ApoE), α-synuclein, Triggering Receptor Expressed on Myeloid cells 2 (TREM2), and other inflammatory markers (CRP, TNF-α, IL-6). High tau (effect size 2.10, 95% CI, I2 = 52%), and p-tau (1.95, I2 = 48%), and a decrease in Ab42 (1.75, I2 = 45%), were each found to have a consistent positive relation with an increased risk of Alzheimer's disease. ApoE e4 (2.50, I2 = 60%), plasma neurofilament light chain (1.60, I2 = 37%), and C-reactive protein (1.30, I2 = 25%) are genetic biomarkers that show significant predictive values.Pre-initial lab biomarkers have a strong correlation with Alzheimer's Disease risk as well and can be used extensively to prognosticate Alzheimer's Disease. Nevertheless, additional studies are needed to elucidate their role in the development of Alzheimer's disease and to develop effective preventive measures.